A Multi‐Signaling Performance for Simultaneous Surveillance and Accretion of Cysteine and Serine in Human Cancer Cell. Issue 1 (17th December 2019) - Kundu, Shampa; Maiti, Pulak Kumar; Sahoo, Prithidipa
Abstract: A unique fluorescence chemosensing method has been introduced to explain a new strategy for simultaneous selective determination of cysteine and serine in two different emission channels through an "on‐off‐on" mechanism. Dansyl chloride‐picolylamine conjugate (DNPC ) ensembles with Cu 2+ (DNPC ‐Cu 2+ ) and shows a turn‐on fluorescence while binding with serine or cysteine. Fluorescence, NMR titrations and DFT calculations has been performed in order to understand the sensing mechanism and the electronic properties of the receptor‐donor complex. The chemosensing method has been successfully applied in human cancer cells to detect and quantify cysteine and serine differentially. Abstract : A unique fluorescence "on‐off‐on" technique has been introduced for simultaneous selective estimation of cysteine and serine in human cancer cells by using two different emission channels.